Opening up the black box: Interacting subspheres through enterprise entry and exit in China - Mária Csanádi; Ferenc Gyuris; Wanjun Wang (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2020)
In this paper, we scrutinize in the transforming party-state system of China the subtle dynamics of enterprise adaptation to state interventions, which react to hardening external and internal constraints. We use a comparative systemic framework that interprets adaptation in the context of system dynamics and transformation (Csanádi, 2006). We analyze a firm-level database of the Chinese industry from 1998 to 2013 with more than 3.8 million entities. Enterprise sensitivity and adaptation is measured by entries and exits. Taking a systemic approach, we distinguish enterprises that belong to either the party-state network or to the market as two economic sub-spheres defined by our analytical framework. Using the dynamics of entries and exits of industrial enterprises in each of these two spheres, we measure their expansion and contraction as well as that of the speed of both. Different speed allows for the quantification of the dynamics of economic transformation. Our results reveal that increasing frequency of entries and exits, both within and between the two spheres, are interconnected with state interventions reacting to booming and cooling periods of system-specific overinvestment and hardening and softening external constraints (Csanádi, 2015; Csanádi and Gyuris, forthcoming). [...]
Keywords: O53; P12; P16; P2; P26; P31; 330; China; system transformation; power network; local power; enterprise behavior; crisis; anti-corruption campaign; state intervention